Synaptic Activity Regulated mRNA-Silencing Foci for the Fine Tuning of Local Protein Synthesis at the Synapse - Pascual, Malena Lucía (2012)
The regulated synthesis of specific proteins at the synapse is important for neuron plasticity, and several localized mRNAs are translated upon specific stimulus. Repression of mRNA translation is linked to the formation of mRNA-silencing foci, including Processing Bodies (PBs) and Stress Granules (SGs), which are macromolecular aggregates that harbor silenced messengers and associated proteins. In a recent work, we identified a kind of mRNA-silencing foci unique to neurons, termed S-foci, that contain the post-transcriptional regulator Smaug1/SAMD4. Upon specific synaptic stimulation, the S-foci dissolve and release mRNAs to allow their translation, paralleling the cycling of mRNAs between PBs and polysomes in other cellular contexts. Smaug 1 and other proteins involved in mRNA regulation in neurons contain aggregation domains distinct from their RNA binding motifs, and we speculate that self-aggregation helps silencing and transport. In addition to S-foci and PBs, other foci formed by distinct RNA binding proteins, such as TDP-43 and FMRP among others, respond dynamically to specific synaptic stimuli. We propose the collective name of synaptic activity-regulated mRNA silencing (SyAS) foci for these RNP aggregates that selectively respond to distinct stimulation patterns and contribute to the fine-tuning of local protein synthesis at the synapse.